1977
DOI: 10.3133/ofr77783
|View full text |Cite
|
Sign up to set email alerts
|

The geological investigation of the Taurus-Littrow Valley: Apollo 17 landing site

Abstract: Astronauts Cernan and Schmitt, of Apollo 17, landed in the Taurus-Littrow valley of the Moon on December 11,1972. Their major objectives were (1) to sample very ancient lunar material such as might be found in pre-Imbrian highlands as distant as possible from the Imbrium basin and (2) to sample pyroclastic materials that had been interpreted as significantly younger than the mare basalts returned from previous Apollo landing sites. The crew worked approximately 22 hours on the lunar surface; they traversed abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(90 citation statements)
references
References 0 publications
2
88
0
Order By: Relevance
“…However, there is no consensus concerning the origin of the aphanites. Some authors have proposed that they are a different facies of Serenitatis melt (Dence et al, 1976;James et al, 1978;Wolfe et al, 1981), but others attribute these rocks to a different, or several different, impacts (Dalrymple and Ryder, 1996). Radiometric age data for the two types overlap within uncertainties and can not resolve separate events (Dalrymple and Ryder, 1996).…”
Section: Apollo 17 Impact Melt Brecciasmentioning
confidence: 94%
“…However, there is no consensus concerning the origin of the aphanites. Some authors have proposed that they are a different facies of Serenitatis melt (Dence et al, 1976;James et al, 1978;Wolfe et al, 1981), but others attribute these rocks to a different, or several different, impacts (Dalrymple and Ryder, 1996). Radiometric age data for the two types overlap within uncertainties and can not resolve separate events (Dalrymple and Ryder, 1996).…”
Section: Apollo 17 Impact Melt Brecciasmentioning
confidence: 94%
“…Wood (e.g., Marvin, 1975;Wood, 1975;Ryder et al, 1975). It consists of two main parts (see summary in Wolfe et al (1981)): a light-gray friable feldspar-rich matrix (e.g., sample 72275) and a dark-gray competent microbreccia (72215 and 72275, and clast within 72275). The dark gray part is interpreted as an older impact breccia incorporated into the light gray matrix (Wolfe et al, 1981).…”
Section: Breccia Samples From the South Massifmentioning
confidence: 99%
“…The Taurus-Littrow Valley, located between two highland massifs called the South and North massifs (Wolfe et al, 1981) was selected as the Apollo 17 landing site because it lies just outside the transient cavity of the Serenitatis impact basin (Head, 1979;Ryder et al, 1997) and is interpreted to overlie the upper part of thick ejecta from this impact (e.g., Wolfe et al, 1981). This is consistent with the composition of boulders at the base of the South Massif which consist of texturally heterogeneous breccias (Simonds, 1975).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Apollo 17 astronauts sampled the regolith at the base of the Sculptured Hills during their last surface traverse at station 8 (latitude 20.278°N, longitude 30.848°S; Robinson and Jolliff 2002). They dug a 25-cm-deep trench (Wolfe et al 1981) that revealed the best preserved lunar regolith stratigraphy collected during the Apollo missions (Mitchell et al 1973; Fig. 1).…”
Section: Regolith Sample Collected At Station 8 Apollo 17mentioning
confidence: 99%